2018
DOI: 10.1248/bpb.b18-00407
|View full text |Cite
|
Sign up to set email alerts
|

Echinacoside, an Active Constituent of <i>Cistanche Herba</i>, Exerts a Neuroprotective Effect in a Kainic Acid Rat Model by Inhibiting Inflammatory Processes and Activating the Akt/GSK3β Pathway

Abstract: Echinacoside is a major compound of Cistanche Herb and has glutamate release-inhibiting activity in the brain. Given the involvement of excitotoxicity caused by massive glutamate in the pathophysiology of epilepsy, we explored the antiepileptic effect of echinacoside on kainic acid-induced seizures in rats. The rats were intraperitoneally administrated echinacoside for 30 min prior to intraperitoneal injection with kainic acid. The results showed that kainic acid induced seizure-like behavioral patterns, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Besides, as a crucial active compound from CH, ECH plays a key role toward neuroprotective activity according to regulating multiple pharmacological mechanisms. ECH improves seizure‐like behavioral patterns by decreasing glutamate concentrations and inhibiting proinflammatory cytokine genes expression 124 . The antiepileptic effect of ECH may be also attributed to the simultaneous decreases of both glutamate release and blockage of abnormal firing synchronization in hippocampal pyramidal neurons 125 .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Besides, as a crucial active compound from CH, ECH plays a key role toward neuroprotective activity according to regulating multiple pharmacological mechanisms. ECH improves seizure‐like behavioral patterns by decreasing glutamate concentrations and inhibiting proinflammatory cytokine genes expression 124 . The antiepileptic effect of ECH may be also attributed to the simultaneous decreases of both glutamate release and blockage of abnormal firing synchronization in hippocampal pyramidal neurons 125 .…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Pretreated 10 or 50 mg/kg echinacoside for 30 min on kainic acid-induced seizures rats can enhance their neuronal survival and prevent epilepsy by inhibiting glutamate excitotoxicity and autophagy, suppressing inflammation, and activating protein kinase B (Akt)/glycogen synthase kinase (GSK) 3β signaling. Therefore, it significantly increased seizure latency more than 1 h and decreased seizure severity (Lu et al, 2018a). A 4-aminopyridine (4-AP)-induced epileptiform activity with an in vitro rat hippocampal neurons' model study reported that echinacoside reduced spontaneous glutamate release, the frequency but not the amplitude of spontaneous excitatory postsynaptic currents, and the sustained repetitive firing of action potentials in hippocampal CA3 pyramidal neurons (Lu et al, 2018b).…”
Section: Cistanche Deserticolamentioning
confidence: 99%
“…Previous studies have shown that the regulation of GSK3β can act as a target and modulator of antidepressant action and may be involved in the pathogenesis of depression. [10][11][12] Cyclin D1 is one of the important substrates of GSK3β. As a key protein for regulating cell cycle and cell proliferation, Cyclin D1 can bind to cyclin dependent kinase 4/6, start DNA synthesis and accelerate cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%